QARAQALPAQ BALALAR OYÍN FOLKLORÍNÍŃ ETNOPEDAGOGIKALÍQ ÓZGESHELIKLERI - Biysenbaev, Q. (ILIM hám JÁMIYET, 2024)
The article emphasizes the educational aspects of game songs belonging to Karakalpak folklore, including children's game folklore, as an independent genre. Ethno-pedagogical features of children's game folklore are also analyzed.